Komodifikasi dalam Ekonomi Politik Media: Studi Kasus pada Instagram Sabrina Chairunnisa - Aldi Hardianto; Indah Sari Pratidina (Koneksi, 2026)
The rapid advancement of digital technology has transformed social media into a capitalization space where identity and creativity are converted into economic exchange value. This study analyzes the commodification processes within the digital activities of influencer Sabrina Chairunnisa through the lens of the political economy of media, specifically applying Vincent Mosco’s conceptual framework. Through a qualitative descriptive approach and case study method, data was collected via virtual observation of Instagram content and documentation to understand how creativity transforms into commercial value. The research reveals that Chairunnisa effectively integrates content creation, labor, and audience interaction to generate economic profit while maintaining ethical work standards without exploitation. Educational skincare reviews and entertainment content transform into commodities that significantly benefit brands like Wardah and JimsHoney, turning personal expression into a strategic marketing tool. Furthermore, the meticulous labor of her creative team and the high engagement of her audience are capitalized upon to strengthen her bargaining power in the competitive influencer marketing industry. This study concludes that social media functions as a complex capitalist ecosystem where digital influence and creative labor are systematically commodified. Pesatnya perkembangan teknologi digital telah mengubah media sosial menjadi ruang kapitalisasi di mana identitas dan kreativitas bertransformasi menjadi nilai tukar ekonomi. Penelitian ini menganalisis proses komodifikasi dalam aktivitas digital influencer Sabrina Chairunnisa melalui perspektif ekonomi politik media dengan menerapkan kerangka konseptual komodifikasi dari Vincent Mosco. Melalui pendekatan deskriptif kualitatif dan metode studi kasus, data dikumpulkan lewat observasi virtual terhadap konten Instagram serta dokumentasi untuk memahami mekanisme kreativitas menjadi komoditas komersial. Hasil penelitian mengungkapkan bahwa Chairunnisa secara efektif mengintegrasikan kreasi konten, tenaga kerja, dan interaksi audiens untuk menghasilkan keuntungan ekonomi sembari tetap mempertahankan standar kerja yang etis tanpa eksploitasi. Konten ulasan edukatif mengenai perawatan kulit dan hiburan bertransformasi menjadi komoditas yang memberikan keuntungan signifikan bagi jenama seperti Wardah dan JimsHoney, sekaligus mengubah ekspresi personal menjadi alat pemasaran strategis. Lebih lanjut, kerja cermat tim kreatifnya serta keterlibatan audiens yang tinggi dikapitalisasi untuk memperkuat posisi tawarnya dalam industri pemasaran influencer yang kompetitif. Studi ini menyimpulkan bahwa media sosial berfungsi sebagai ekosistem kapitalis yang kompleks di mana pengaruh digital dan kerja kreatif dikomodifikasi secara sistematis.